2021
DOI: 10.1007/978-3-030-67084-9_5
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Agility in IT Project Portfolios – A Systematic Literature Review

Abstract: Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…In line with (Puthenpurackal Chakko et al, 2021), we have identified 3 contributions to research and practice in this study, as a response to the research question (stated in section 3.1.) 1.-To have an adaptive portfolio management model (APM) that senses and responds to changes in the market.…”
Section: Implications Of Findingsmentioning
confidence: 81%
See 1 more Smart Citation
“…In line with (Puthenpurackal Chakko et al, 2021), we have identified 3 contributions to research and practice in this study, as a response to the research question (stated in section 3.1.) 1.-To have an adaptive portfolio management model (APM) that senses and responds to changes in the market.…”
Section: Implications Of Findingsmentioning
confidence: 81%
“…Other important academic papers giving us a broad overview of the application of PPM at the enterprise level are: (Stettina & Hörz, 2015) which proposes 4 domains of practice for structuring a PPM process by introducing: (1) strategize and roadmap, (2) identify and funnel, (3) review, prioritize and balance, and (4) Allocate and delegate. (Ahmad et al, 2017) which provides an overview of the different tools and methods for addressing PPM processes in Lean and Agile organisational contexts and, (Puthenpurackal Chakko et al, 2021) which identified several aspects of PPM impacted by Agile delivery practices.…”
Section: Introductionmentioning
confidence: 99%
“…If the portfolio seldom delivers value, the investment in discovery may become a sunk cost, negatively impacting the portfolio's financial performance. Agile principles must be embraced to counter this risk, prioritizing regular value delivery [40]. This strategy ensures that resources committed to the discovery and planning stages are effectively used and yield a positive return on investment.…”
Section: Discussionmentioning
confidence: 99%
“…When developing and justifying the case for investment in business architecture, it should take account of value over the long-term, which should be at least 5 years. This is likely to be challenging for many organisations where their investment portfolio may be oriented towards shorter horizons for the evaluation of return on investment (Puthenpurackal Chakko, Huygh, & De Haes, 2021).…”
Section: Years Of Adoption (Adoption)mentioning
confidence: 99%
“…This underscores the importance of effective resource allocation, strategic commitment, and visionary leadership in translating organisational potential into tangible strategic results. It emphasizes the pivotal role of Business Architecture leaders in crafting a compelling vision, engaging senior leaders, and maintaining effective communication over a sustained time horizon (>5 years) to successfully mature the Business Architecture practice (Collis & Montgomery, 2008;Puthenpurackal Chakko, Huygh, & De Haes, 2021).…”
Section: Organisational Size (Size_rev and Size_emp)mentioning
confidence: 99%